Libertarian views on intellectual property law - Soepboer, Mick (Department of Commercial Law, 2014)
During the elections for the European Parliament in June 2009, an unknown party in Sweden turned out to be very successful. The Pirate Party, campaigning for patents to be scrapped and copyright to last just five years instead of 70, received 7% of the votes in the Scandinavian country, giving the party the right to a seat in the Parliament in Brussels. These modern day pirates are most successful in Sweden, but similar parties exist in the United States and a number of European countries as well. In modern society, copyrights, patents, and other forms of intellectual property play a bigger role in normal life than they did one or two decades ago. This development makes people more aware of all the effects of intellectual property theory and policy cause. It also brings up the discussion concerning whether the original goals of the policies are still being pursued properly. Is the chosen path in IP law still a valid one in this digital age or is it time to rethink the structure?